Artificial chamber and 3D printed iris: a new wet lab model for teaching Descemet's membrane endothelial keratoplasty. Issue 2 (26th September 2018) - Famery, Nicolas; Abdelmassih, Youssef; El‐Khoury, Sylvain; Guindolet, Damien; Cochereau, Isabelle; Gabison, Eric E.
Abstract: Purpose: To describe a new wet lab model of Descemet membrane endothelial keratoplasty (DMEK) using human corneas mounted on an artificial anterior chamber with an artificial iris and to compare the performance time and scores between beginners and experienced anterior segment surgeons. Methods: Corneas were mounted on an artificial chamber. To simulate an anterior chamber and to avoid loosing the graft into the tubing, a 3D printed iris was added. Each DMEK procedure required only one cornea for graft preparation, insertion, orientation, unfolding and centration. Ten human research corneas were used for training purposes. Intraoperative OCT was only used to validate the different steps of the procedure. Operators were divided into two groups, two beginners and three experienced DMEK surgeons. Results: All DMEK procedures were successfully performed. Descemet's tears were frequent but harvesting was successful in all procedures. All combinations of graft unfolding techniques were possible. Experienced surgeons performed statistically better then beginners with faster harvesting (12.8 versus 28.2 min; p = 0.02) and insertion (13.5 versus 20.8 min; p = 0.05) times and better performance score (94 versus 52; p = 0.03). Conclusion: This DMEK wet lab model offers a close to reality, feasible, resource‐sparing and valid teaching technique that permits to perform all DMEK surgical steps. It also offers the possibility of varying the surgical difficulty by changing the anterior chamber depth.